Indonesian National Army Involvement in Handling Terrorism Action from Legal Perspective - Wilma Silalahi (Constitutionale, 2021)
The crime of terrorism is an extraordinary crime against humanity, including a “serious crime” whose number of actions has increased. It requires handling with exceptional measures and "serious measures" with still respecting human values. Thus, what becomes an interesting problem in this research is how to involve the Indonesian National Army in handling acts of terrorism from a legal perspective. This research uses a normative doctrinal method. The Indonesian National Army's involvement in managing acts of terrorism and supported by the prevailing laws and regulations provides a greater sense of security and legal certainty for the community. Also, this research intends to examine that the involvement of the Indonesian National Army in handling acts of terrorism is by applicable regulations. The handling of criminal acts of terrorism requires a juridical basis to create a sense of security and justice. Thus, the Indonesian National Army must maintain the Unitary State of the Republic of Indonesia's territorial integrity and uphold state sovereignty. Therefore, the involvement of the Indonesian National Army in the context of handling acts of terrorism is an aid to the PolicePolice in defending the independence of the state, maintaining the territorial integrity of the Unitary State of the Republic of Indonesia, and protecting the entire nation and all spilled Indonesian blood based on Pancasila and the 1945 Constitution. The involvement of the Indonesian National Army in eradicating acts of terrorism is part of the support for the National Police, in the context of carrying out law enforcement operations that are not Military Operations Apart from War, unless they develop into acts of terrorism that threaten the existence of the Unitary State of the Republic of Indonesia or extraordinary circumstances occurs. This is in line with the Indonesian National Army's unique nature (lex specialis) in carrying out its duties.